Strengthening of Agricultural Labor Based on Local Wisdom Model Besiru in East Lombok District - Muhammad Joni Iskandar; Muhammad Anwar; Ria Ashari (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Labor is an essential factor of production in running a farm. Production produced by farmers depends on the availability of sufficient labor so that efficiency is achieved. However, the demand for labor is currently high while the supply is low. Therefore, there is a labor crisis in the agricultural sector. Its limited availability is caused by labor regeneration, which is still difficult to implement considering that the younger generation is not interested in working as farmers and chooses other professions. This study aims to analyze farmers' response to agricultural labor based on the local wisdom of the Besiru model in East Lombok Regency. This type of research is descriptive analysis research to explain the actual conditions of agricultural labor based on the local wisdom of the Besiru model. The research location was purposely determined to be in Batu Putik Village, Keruak District, considering that farmers still use Besiru in running their farming business. The research sample of 30 farmers was determined by census in the Bareng Bersinar Farmer Group I and the Bareng Bersinar Farmer Group II. The method for estimating farmer responses to the Besiru model labor system uses the empathy, persuasion, impact, and communication (EPIC) model with Likert's Summated Rating Scale (LSRS), where each choice of answers is given a score. The results showed that most farmers' cognitive, affective, and conative responses to the Besiru model labor were as expected.